A Parabola on the Tuscan Landscape: New Gazes of the Amateur Photography in the 1920s - Gitto, Fabrizio (Aesthetica Preprint, 2024)
The contribution investigates the cultural dynamics and spaces of expression that, during the 1920s, made amateur photography the most effective medium for creating and disseminating a new image of the Tuscan landscape. In this decade, landscape photography played a leading role in various publishing and exhibition projects in Tuscany, such as the magazine “Illustrazione Toscana” (1923-1945), the two editions of the Florentine Esposizione Fotografica del paesaggio toscano (1925, 1927), and the book Toscana (1927). If, at the beginning of the 1920s, the official visual panoramas of the region were constructed and transmitted by professional photographic studios, in the following years, renewed visions of Tuscany were promoted through its non-monumental aspects, mainly due to amateur photographers, such as Vittorio Alinari, Lodovico Pachò, Gino Danti, and Ermanno Biagini.